The Impact of Halal Tourism on Community Welfare in the Leading Tourism Destination of Sawarna Banten : N-Vivo Analysis - Itang; Ahlam Tri Anugrah (Lead Journal of Economy and Administration, 2025)
Halal tourism is a new phenomenon in tourism that continues to increase along with the increasing number of Muslim tourists. Halal tourism is included in economic development that aims to expand and equalize business opportunities, employment and community welfare. The welfare of the community in question is a condition where a person can meet basic needs such as food, clothing, shelter, clean drinking water and the opportunity to continue their education and have a decent job to support their quality of life so that they are free from poverty, ignorance, fear, or worry so that their lives are safe and peaceful, both physically and mentally. This study uses a qualitative research method with a descriptive analysis research type. The data analysis technique in this study uses the help of the Nvivo 15 application with a four-stage data analysis process, namely: data import, data coding, data visualization, and data extraction. The results of the study showed that there was very little impact felt from the benefits of halal tourism on local welfare in the Sawarna tourist destination, this is evidenced by the standard quality of life, the small number of tourists, less than optimal management of tourist areas, standard economy, no new socialization policies, bad issues and natural conditions.